FACTORS AFFECTING THE ACCEPTANCE OF ELECTRONIC WALLET OVO IN INDONESIA - Ariyanti, Dina; Suryawati, Rindah; Sya’bania, Anisa (Jurnal Mebis, 2023)
OVO is an electronic wallet that has been issued by PT. International Visionet. It can be used to accommodate various needs related to mobile and cashless payments. The number of these applications is quite large and shows significant growth since the first user launch in Indonesia. The purpose of this study was to determine the factors that affect the acceptance of electronic wallet OVO in Indonesia with the Technology Acceptance Model approach. Analysis Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was used to test the hypothesis. Results reveal that factors influencing the intention to use OVO are perceived usefulness, perceived convenience, trust, user attitude, and risk. Risk factors can reduce trust and correlate with the intention to use. Whereas user intention can increase the actual use of electronic wallets OVO. The practical implication of the research is that the trust factor could increase the intention to use an OVO electronic wallet. Therefore companies need to increase public trust in OVO. The risk could reduce trust but that was not the main factor influencing public trust in OVO electronic wallets. Perceived ease of use provided the greatest influence on the perceived usefulness of an OVO electronic wallet. Companies need to consider trust, convenience, perceived benefits, and risks to increase OVO acceptance in the community.